Long term follow up of patients treated for Helicobacter pylori infection. Issue 11 (28th June 2005) - Mera, R; Fontham, E T H; Bravo, L E; Bravo, J C; Piazuelo, M B; Camargo, M C; Correa, P
Abstract : Background: Helicobacter pylori infection induces progressive inflammatory changes in the gastric mucosa that may lead to gastric cancer. Understanding long term effects resulting from the cure of this infection is needed to design cancer prevention strategies. Methods: A cohort of 795 adults with preneoplastic gastric lesions was randomised to receive anti- H pylori treatment and/or antioxidants. At the end of six years of intervention, those who did not receive anti- H pylori treatment were offered it. Gastric biopsies were obtained at baseline, and at 3, 6, and 12 years. A histopathology score was utilised to document changes in gastric lesions. Non-linear mixed models were used to estimate the cumulative effect of H pylori clearance on histopathology scores adjusted for follow up time, interventions, and confounders. Results: Ninety seven per cent of subjects were H pylori positive at baseline, and 53% were positive at 12 years. Subjects accumulated 1703 person years free of infection. A multivariate model showed a significant regression in histopathology score as a function of the square of H pylori negative time. Subjects who were H pylori negative had 14.8% more regression and 13.7% less progression than patients who were positive at 12 years (p = 0.001). The rate of healing of gastric lesions occurred more rapidly as years free of infection accumulated, and was more pronounced in less advanced lesions. Conclusions: Preneoplastic gastric lesions regress at a rate equal to the square of time in patients rendered free of H pylori infection. Our findings suggest that patients with preneoplastic gastric lesions should be treated and cured of their H pylori infection.